Total body irradiation's dosimetric features by volumetric modulated ARC therapy method. (September 2016) - Tas, B.; Durmus, I.F.; Ozturk, S. Tokdemir
Abstract : Purpose: To compare three different types of volumetric modulated arc therapy(VMAT) planning tecniques using Elekta Versa HD lineer accelerator to deliver total body irradition(TBI) treatment. Methods: Five TBI patient's treatment planning performed using Monaco5.1® treatment planning system with three different VMAT tecniques for each patient.First one was single arc VMAT tecnique, second one was double arc VMAT tecnique and third one was 2 fields arc VMAT tecnique for one isocentre.The VMAT-TBI tecnique consisted of three isocentres and three overlapping arcs.The prescribed dose was 95% of target volume receiving dose of 12 Gy.Mean dose to lung and kidney were restricted less than 9.0 Gy. Results: An average total delivery time was determined 835 ± 86 seconds and an average monitor unit (MU)s was determined 2202 ± 254 MUs for double arc VMAT technique. This study demonstrates that double arc VMAT technique has got less MUs than other technique but an average delivery time is %17 more than single arc VMAT technique. When we compared organ at risk (OAR)s, we had less dose and better dose coverage to target with double arc VMAT technique. Conclusion: The tecnique for TBI using VMAT was found feasible.The results show that dose coverage of target and OAR's doses also depend significantly VMAT techniques. Based on the results we have decided to plan TBI in our clinic with double arc VMAT technique.